Criticism minima: how to overcome ethical in yourself. Book review: Claire Bishop. Artificial Hells: Participatory Art and the Politics of Spectatorship. London: Verso, 2012. (ISBN 9781844676903) - Калугер, Анна (Київський національний університет імені Тараса Шевченка, 2019)
This review is an attempt of a critical generalization of the first monograph devoted to the phenomenon of Participatory Art – «Artificial Hells: Participatory Art and the Politics of Spectatorship» by Claire Bishop. Аuthor focuses on the problems of the binary of active and passive viewing, art after a «Social turn», the concept of ethics and the phenomenon of theatricalization in contemporary art.

Рецензія становить спробу критичного огляду книги Клер Бішоп "Штучні пекла", яка є першою монографією, присвяченою феномену партиципаторного мистецтва.
Критика minima: як подолати в собі етичне. Рецензія на книгу «Штучні пекла. Партиципаторне мистецтво та політика глядацтва» Клер Бішоп